Loss of substantia nigra hyperintensity on 7 Tesla MRI of Parkinson's disease, multiple system atrophy, and progressive supranuclear palsy. (May 2016) - Kim, Jong-Min; Jeong, Hye-Jin; Bae, Yun Jung; Park, Sung-Yeon; Kim, Eunhee; Kang, Seo Young; Oh, Eung Seok; Kim, Kyeong Joon; Jeon, Beomseok; Kim, Sang Eun; Cho, Zang-Hee; Kim, Young-Bo
Abstract: Background: Seven Tesla (7T) MRI can visualize anatomical alterations occurring in a hyperintense structure of the substantia nigra in Parkinson's disease (PD). Objective: We investigated whether 7T MRI can detect the loss of substantia nigra hyperintensity in patients with PD, multiple system atrophy (MSA), and progressive supranuclear palsy (PSP). Methods: Using 7T MRI, we evaluated 26 healthy subjects, 30 patients with PD, 7 patients with MSA, and 3 patients with PSP. Two blinded readers independently assessed the images. We carried out a comparative analysis of five patients with hemiparkinsonism via 123 I-2β-carbomethoxy-3β-(4-iodophenyl)-N-(3-fluoropropyl)-nortropane ( 123 I-FP-CIT) SPECT. Results: 7T MRI revealed a definitive shape of nigral hyperintensity in healthy subjects, nearly identical to neuropathological characterization of nigrosome 1, and enabled instantaneous determination of its presence or absence in all subjects. Nigral hyperintensity was lost in all patients with PD, MSA with predominant parkinsonism, and PSP. One of five patients with MSA with predominant cerebellar ataxia showed an intact nigral hyperintensity. The side effects were mild and tolerable, and imaging was successful in patients with dyskinesia. Motion artifact incidence was higher in elderly subjects. In hemiparkinsonism cases, we observed partial loss of nigral hyperintensity on the side of less reduced 123 I-FP-CIT binding, suggesting an ongoing iron deposition on the unaffected side in hemiparkinsonism. Conclusions: The present findings suggest that 7T MRI represents an excellent tool for evaluating nigral hyperintensity in PD, MSA, and PSP, with tolerable side effects and limited motion artifacts. Thus, imaging of parkinsonism may benefit from using 7T MRI. Graphical abstract: Highlights: 7T MRI enabled unambiguous identification of nigral hyperintensity in all subjects. Nigral hyperintensity was lost in all patients with PD, MSA-P, and PSP. One out of five patients with MSA-C showed intact nigral hyperintensity. Side effects from 7T and motion artifacts were mild and tolerable. In hemiparkinsonism, partial loss of nigral hyperintensity was observed.